2021
DOI: 10.1055/s-0041-1735270
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Anastomotic Leak

Abstract: Anastomotic leaks after colorectal surgery is associated with increased morbidity and mortality. Understanding the impact of anastomotic leaks and their risk factors can help the surgeon avoid any modifiable pitfalls. The diagnosis of an anastomotic leak can be elusive but can be discerned by the patient's global clinical assessment, adjunctive laboratory data and radiological assessment. The use of inflammatory markers such as C-Reactive Protein and Procalcitonin have recently gained traction as harbingers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…A gold standard for diagnosing AL is currently lacking. The diagnosis of an AL generally requires patient’s global clinical assessment, adjunctive laboratory data, and radiological assessment, and the decision of a diagnosis sometimes can be different depending on physicians’ clinical judgment [ 28 , 29 ]. In a retrospective observational study based on the review of patient’s medical records, without an adjudication process in place, investigators’ knowledge of exposure status and study hypothesis (i.e., unblinded outcome classification) could have resulted in potential for differential misclassification of AL, particularly for less severe AL.…”
Section: Discussionmentioning
confidence: 99%
“…A gold standard for diagnosing AL is currently lacking. The diagnosis of an AL generally requires patient’s global clinical assessment, adjunctive laboratory data, and radiological assessment, and the decision of a diagnosis sometimes can be different depending on physicians’ clinical judgment [ 28 , 29 ]. In a retrospective observational study based on the review of patient’s medical records, without an adjudication process in place, investigators’ knowledge of exposure status and study hypothesis (i.e., unblinded outcome classification) could have resulted in potential for differential misclassification of AL, particularly for less severe AL.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies revealed that CRP was uniformly elevated in patients post-colorectal surgery but typically normalized by POD 3. 75 CRP have also been shown, in a meta-analysis of seven studies, to have a high negative predictive value for leak (NPV = 97%) when a cut-off of 172 mg/L on POD 3 was used. 77 The trajectory of CRP was investigated by a group from Newcastle, Australia.…”
Section: Diagnosis Of Anastomotic Leakmentioning
confidence: 99%
“…Symptoms and signs of anastomotic leak typically include increasing abdominal pain, nausea and vomiting, fever, tachycardia, peritonitis, and prolonged ileus. 75 These signs and symptoms may not be apparent until POD 5. 76 Biochemically, inflammatory markers are typically elevated with high white cell count (with neutrophilia) as well as elevated C-reactive protein (CRP).…”
Section: Diagnosis Of Anastomotic Leakmentioning
confidence: 99%
See 1 more Smart Citation
“…The branches of this tree represent the management protocols employed by the Coloproctology Unit in cases of anastomotic leakage, drawing from our own experience and supported by recently published studies. [21][22] Direct costs related to diagnostic and therapeutic procedures were computed for each patient based on medical record review conducted by the primary authors of the study. Indirect costs such as sick leave, reduced productivity, and psychological damage were not included due to the challenges associated with quantifying them.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%